Tradisi Ngalap Berkah dalam Perayaan Grebeg Syawal di Keraton Kanoman Cirebon (Studi Mengenai Makna Budaya dan Sufistik) - Nurul Hamim; Wasil Wasil (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research was written to analyze the cultural and Sufistic meaning contained in the Ngalap Berkah tradition in the Grebeg Syawal celebration at the Kanoman Palace, Cirebon. This type of research is qualitative research using interviews and field observations. This research uses Bronislaw Malinowski's anthropological approach. The results of this research can be found that culturally, the Ngalap Berkah tradition reflects harmony between the spiritual and social life of the Cirebon people. From a Sufistic perspective, this tradition contains the meaning of blessing which is believed to be obtained through purity and cleanliness of heart in doing good to others. The Islamic values contained in this tradition include the concepts of almsgiving, ukhuwah , and taqwa.